Workshop Pemanfaatan Kahoot dalam Pembelajaran Matematika di Sekolah: Pengabdian - Zulfah; Astuti; Fitri Amelia Hermansyah; Novita Sari; Syaira Amelya (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The Kahoot Utilization Workshop in Mathematics Learning in schools addressed teachers' challenges in integrating digital technology. The main objective was to train teachers to design and implement innovative and effective mathematics learning using Kahoot. The method used in this activity consisted of four stages: planning, implementation, observation and evaluation, and reflection. The planning stage included coordination with the Head of the Mathematics Education Study Program, preparation of Workshop materials, and proposal submission. The implementation stage involved forming teacher groups, delivering Workshops according to the schedule, and mentoring by students for teachers experiencing difficulties. Observation and evaluation were conducted to measure success and identify obstacles, while reflection was conducted jointly by the implementation team and partner teachers to evaluate the overall process. Through this Workshop, teachers demonstrated high enthusiasm and successfully understood how to create quizzes and interactive activities using the application. As a result, they became more confident in integrating Kahoot into the classroom, creating a more dynamic learning environment and motivating students, despite technical challenges such as limited devices and internet connection.